Keabsahan Perjanjian Financial Technology Lending Dengan Konsep Kontrak Roscoe Pound - Imelda Martinelli; Michelle Audrey Serena; Natashya Natashya (LPPM Universitas Ekasakti Padang, 2023)
The era of technology has given birth to significant transformation in the financial sector, particularly in the form of Financial Technology Lending (Fintech Lending). Fintech Lending is the result of the fusion of technology and the financial sector, enabling individuals and businesses to access loans quickly, easily, and transparently. Specifically, this journal discusses the validity of Fintech Lending agreements from the perspective of civil law and other legal aspects related to Fintech Lending agreements. Using a normative legal research method and supported by relevant secondary data on the validity of Financial Technology Lending agreements, collected, selected, and processed as the primary data source in this study, as well as the development of descriptive-analytical research based on applicable legal regulations. This is analyzed with legal theories related to issues or problems in Financial Technology Lending. This journal examines the validity of agreements through the Civil Code Book Articles 1313, 1314, and 1320, Financial Services Authority Regulation No. 77 of 2016 Article 1 Number 3, Law No. 11 of 2008 concerning Electronic Information and Transactions Article 1 Number 17 and Article 18. The validity of a Fintech Lending agreement is also correlated with the concept of contracts as proposed by Roscoe Pound through four theories, namely, the Will Theory, the Bargain Theory, the Equivalent Theory, and the Injurious-Reliance Theory. Efforts to establish a Fintech Lending Data Center (Pusdafil) which aims to monitor and manage risks. These steps demonstrate efforts to secure the online loan process and protect the parties involved from possible fraud or default.